2010
DOI: 10.1128/jb.00650-10
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Biofilms Facilitate Horizontal DNA Transfer between Strains ofMycobacterium smegmatis

Abstract: Conjugal transfer of chromosomal DNA between strains of Mycobacterium smegmatis occurs by a novel mechanism. In a transposon mutagenesis screen, three transfer-defective insertions were mapped to the lsr2 gene of the donor strain mc 2 155. Because lsr2 encodes a nonspecific DNA-binding protein, mutations of lsr2 give rise to a variety of phenotypes, including an inability to form biofilms. In this study, we show that efficient DNA transfer between strains of M. smegmatis occurs in a mixed biofilm and that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…We found that plasmid pB10 could efficiently invade floating pellicles as well as surface-attached biofilms close to this interface. Recently, Nguyen et al showed that transfer of chromosomal markers among Mycobacterium smegmatis strains also occurred predominantly at the air-liquid interface (52).…”
Section: Discussionmentioning
confidence: 99%
“…We found that plasmid pB10 could efficiently invade floating pellicles as well as surface-attached biofilms close to this interface. Recently, Nguyen et al showed that transfer of chromosomal markers among Mycobacterium smegmatis strains also occurred predominantly at the air-liquid interface (52).…”
Section: Discussionmentioning
confidence: 99%
“…For example, QAC resistance genes carried by transferable genetic elements have been widely identified (Bjorland et al 2001;Gillings et al 2009;Elhanafi et al 2010). Different studies have generated evidence suggesting that biofilms may constitute an optimum environment for the exchange of genetic material (Hausner and Wuertz 1999;Maeda et al 2006;Ando et al 2009;Nguyen et al 2010), leading to the dissemination of biocide resistance cassettes within the population. Indeed, high cell density, the presence of a matrix, the release of large quantities of DNA or nutrient conditions within biofilms may promote conjugation and transformation processes.…”
Section: Gene Transfers and Mutationsmentioning
confidence: 99%
“…Development of mycobacterial biofilms is promoted in the presence of iron and copper (31,32). At least 1 M ferrous sulfate is required for M. smegmatis biofilm formation, and our standard biofilm culture medium contains 178 M iron.…”
Section: Volume 288 • Number 33 • August 16 2013mentioning
confidence: 99%
“…However, we noted differences when the two strains were cultivated in standing culture in medium lacking Tween 80. Surfactants and detergents are known inhibitors of biofilm formation (30,31). Wild-type M. smegmatis grown under biofilm-inducing conditions formed a pellicle or film at the air-liquid interface 3 days post-inoculation that developed further into a reticulated biofilm (Fig.…”
Section: Smegmatis Mutant Mmpl11 Forms Altered Biofilms-we Demonstmentioning
confidence: 99%